Training on Oyster Mushroom Cultivation for Tadris Biology Students in Developing an Independent Entrepreneurial Spirit - Meyninda Destiara; Nurul Himmah; Istiqamah (Yayasan Sembilan Pemuda Indonesia, 2022)
Oyster mushrooms (Pleurotus ostreatus) are a product related to conventional biotechnology where the product is a food that can be consumed. Oyster mushroom (Pleurotus ostreatus) cultivation training is a community service effort related to conventional biotechnology, which is a food that can be consumed. This training stage includes biotechnology and biological entrepreneurship courses, which aim to develop capabilities in developing biology-based businesses. With this training, it is hoped that you will gain knowledge about oyster mushroom cultivation, as a product related to conventional biotechnology, and know how to implement it in entrepreneurship.